Protein kinase Cδ amplifies ceramide formation via mitochondrial signaling in prostate cancer cells - Sumitomo, Makoto (American Society for Clinical Investigation, 2002)
We studied the role of protein kinase C isoform PKCδ in ceramide (Cer) formation, as well as in the mitochondrial apoptosis pathway induced by anticancer drugs in prostate cancer (PC) cells. Etoposide and paclitaxel induced Cer formation and apoptosis in PKCδ-positive LNCaP and DU145 cells but not in PKCδ-negative LN-TPA or PC-3 cells. In contrast, these drugs induced mitotic cell cycle arrest in all PC cell lines. Treatment with Rottlerin, a specific PKCδ inhibitor, significantly inhibited drug-induced Cer formation and apoptosis in LNCaP cells, as did overexpression of dominant negative–type PKCδ. Overexpression of wild-type PKCδ had an opposite effect in PC-3 cells. Notably, etoposide induced biphasic Cer formation in LNCaP cells. The early and transient Cer increase resulted from de novo Cer synthesis, while the late and sustained Cer accumulation was derived from sphingomyelin hydrolysis by neutral sphingomyelinase (nSMase). Cer, in turn, induced mitochondrial translocation of PKCδ and stimulated the activity of this kinase, promoting cytochrome c release and caspase-9 activation. Furthermore, the specific caspase-9 inhibitor LEHD-fmk significantly inhibited etoposide-induced nSMase activation, Cer accumulation, and PKCδ mitochondrial translocation. These results indicate that PKCδ plays a crucial role in activating anticancer drug–induced apoptosis signaling by amplifying the Cer-mediated mitochondrial amplification loop.